2016
DOI: 10.1111/een.12325
|View full text |Cite
|
Sign up to set email alerts
|

Density‐mediated indirect interactions alter host foraging behaviour of parasitoids without altering foraging efficiency

Abstract: Abstract. 1. Foraging decisions of parasitoids are influenced by host density via density-mediated indirect interactions. However, in the parasitoid's environment, non-suitable herbivores are also present. These non-hosts also occur in different densities, which can affect a parasitoid's foraging behaviour.2. The influence of non-host densities can be expressed during the first phase of the foraging process, when parasitoids use plant volatiles to locate plants infested by their host. They may also play a role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…This memory guides C. glomerata to subsequent host patches, but due to the high similarity of HIPV of host and non-host species, these wasps are often unable to discriminate between them (Geervliet et al, 1996;Vos et al, 2001;Bukovinszky et al, 2012), even after oviposition experience (Vosteen et al, manuscript in preparation). The presence of non-host on host plant species has been found to lead to reduced foraging efficiency (Vos et al, 2001;Bukovinszky et al, 2012;De Rijk et al, 2016b;Desurmont et al, 2018;Vosteen et al, manuscript in preparation).…”
Section: Introductionmentioning
confidence: 99%
“…This memory guides C. glomerata to subsequent host patches, but due to the high similarity of HIPV of host and non-host species, these wasps are often unable to discriminate between them (Geervliet et al, 1996;Vos et al, 2001;Bukovinszky et al, 2012), even after oviposition experience (Vosteen et al, manuscript in preparation). The presence of non-host on host plant species has been found to lead to reduced foraging efficiency (Vos et al, 2001;Bukovinszky et al, 2012;De Rijk et al, 2016b;Desurmont et al, 2018;Vosteen et al, manuscript in preparation).…”
Section: Introductionmentioning
confidence: 99%
“…In two-choice assays C. glomerata often preferred dual infested plants that contained host plus non-host herbivores over non-host-infested plants (Shiojiri et al 2000 ; Bukovinszky et al 2012 ; De Rijk et al 2016a , b , c ). Similarly, foraging efficiency was not influenced by non-host-infested plants if the hosts were feeding on a dual infested plant (De Rijk et al 2016b , c ; but see Bukovinszky et al 2012 ). These studies suggest that C. glomerata is adapted to forage in the presence of non-host-infested plants if the hosts feed together with non-hosts on the same plant.…”
Section: Discussionmentioning
confidence: 99%
“…However, the emission of attractive volatiles is not limited to the infested stem part but systemically occurs throughout the plant, even in undamaged leaves (Potting et al., ). In the host location process, the density and feeding position of non‐hosts on a plant negatively affect the first phase (locating host habitat) of the foraging process of Cotesia glomerata (L.), but the second phase (finding a host on the plant) and the overall foraging efficiency of the parasitoid had no influence (de Rijk et al., ,b). Furthermore, we found that a large number of non‐host‐infested plants can affect the host‐searching efficiency of C. kariyai during the first phase, but we were unable to draw conclusions about the second phase yet.…”
Section: Discussionmentioning
confidence: 99%